2010
DOI: 10.1098/rsif.2010.0207
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of single chondrocytes and chondrons determined by micromanipulation and finite-element modelling

Abstract: A chondrocyte and its surrounding pericellular matrix (PCM) are defined as a chondron. Single chondrocytes and chondrons isolated from bovine articular cartilage were compressed by micromanipulation between two parallel surfaces in order to investigate their biomechanical properties and to discover the mechanical significance of the PCM. The force imposed on the cells was measured directly during compression to various deformations and then holding. When the nominal strain at the end of compression was 50 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 51 publications
(111 reference statements)
2
51
0
Order By: Relevance
“…Axial symmetry has been successfully used in previous computational studies to minimize computational cost (Caille et al 2002;Nguyen et al 2010;Ofek et al 2009;Haider and Guilak 2002;Rowat et al 2005). A previous 3D investigation of the role of SF contractility in the compression resistance of cells ,which used the material model employed in the current study, reported similar trends for axisymmetric and polarised cell geometries ).…”
Section: Simulations Reveal Thatsupporting
confidence: 53%
“…Axial symmetry has been successfully used in previous computational studies to minimize computational cost (Caille et al 2002;Nguyen et al 2010;Ofek et al 2009;Haider and Guilak 2002;Rowat et al 2005). A previous 3D investigation of the role of SF contractility in the compression resistance of cells ,which used the material model employed in the current study, reported similar trends for axisymmetric and polarised cell geometries ).…”
Section: Simulations Reveal Thatsupporting
confidence: 53%
“…While there have been many mechanical property measurements of viscoelasticity in cartilage 36 , chondrons 37,38 , and chondrocytes 39,40 , this mechanotransduction study examined how the matrix viscoelasticity impacts chondrocyte behavior. Previous studies have found limited proliferation and deposition of cartilage matrix by chondrocytes encapsulated in non-degradable or slowly-degrading hydrogels of PEG 12 , agarose 13 , alginate 41 and hyaluronic acid 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The neo-Hookean (NH) model, also known as the Gaussian model, is one of the most widely used nonlinear elastic (or hyperelastic) models owing to its simplicity. For example, it has been successfully used to model the deformation of single cells in cytocompression tests [66]. For incompressible materials, the NH model has the following energy function [67] …”
Section: Elastic Modelmentioning
confidence: 99%